2010
DOI: 10.1021/jm900776m
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of Dengue Virus Methyltransferase: Discovery by in Vitro-Driven Virtual Screening on a Desktop Computer Grid

Abstract: Dengue fever is a viral disease that affects 50-100 million people annually and is one of the most important emerging infectious diseases in many areas of the world. Currently, neither specific drugs nor vaccines are available. Here, we report on the discovery of new inhibitors of the viral NS5 RNA methyltransferase, a promising flavivirus drug target. We have used a multistage molecular docking approach to screen a library of more than 5 million commercially available compounds against the two binding sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 49 publications
(106 reference statements)
2
52
0
Order By: Relevance
“…Nevertheless, Podvinec et al reported that two compounds with no guanosine moiety bound to the SAM binding site (IC 50 of 4.4 and 9.5 µM) [31]. Our results confirm the findings by Podvinec et al in that none of the compounds we discovered contain a guanosine moiety.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, Podvinec et al reported that two compounds with no guanosine moiety bound to the SAM binding site (IC 50 of 4.4 and 9.5 µM) [31]. Our results confirm the findings by Podvinec et al in that none of the compounds we discovered contain a guanosine moiety.…”
Section: Discussionsupporting
confidence: 90%
“…Research institutions in developed countries have launched a number of grid-based drug discovery efforts [29-31]; however, similar facilities often do not exist in developing countries. This fact motivated us to utilize two web-based drug-like compound databases (EDULISS and LIDAEUS) for the screening of commercially available chemical compounds as potential inhibitors of dengue NS5 MTase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the metric of early performance to compare the Vina-, NNScore-, and HTVS-based protocols to a common multi-tiered Glide protocol (HTVS–SP–XP) 34 that has been used extensively in the literature (see, for example, refs (52), (55), (56), and (57)). The top 50% best ligands as judged by the HTVS–HTVS protocol were subsequently redocked with Glide SP.…”
Section: Resultsmentioning
confidence: 99%
“…This group includes curcumin [31][32][33], parthenolide [34][35][36][37][38], and RG108-1 [39], a maleimide analogue of RG108 (vide infra); (3) non-nucleoside and non-covalent blockers such as hydralazine [40][41][42][43][44], procaine [45][46][47], procainamide [41,48], (-)-epigallocatechin-3-gallate (EGCG) [49][50][51][52][53], and mahanine [54,55]; and (4) non-covalent blockers identified from virtual screening such as RG108 [56][57][58] and NSC14778 [59,60]. Some of these compounds are drugs approved for other indications such as hydralazine, procaine, and procainamide (vide infra).…”
Section: Introductionmentioning
confidence: 99%